Comparison of Students' Learning Motivation Based on Exact Sciences and Non Exact Sciences Faculty and Gender - Vina Yulia Anhar; Muhammad Rusmin Nuryadin; Novaria Maulina; Fauzie Rahman; Ranindy Qadrinnisa (Universitas Lambung Mangkurat, 2025)
Organizations need to have human resources ready to take on leadership roles and support growth and sustainability. These resources are students who are vital assets so that it needs to be continuously pursued so that students can achieve maximum achievement. High achievement motivation can help students in obtaining high achievement. This study aims to determine the relationship between gender, faculty, and student achievement motivation at university. The research design is quantitative with a cross sectional design. The research sample was 108 Lambung Mangkurat University students from various faculties with proportional random sampling technique. Data analysis used Chi-Square test. The results showed a significant relationship between gender and faculty type on student achievement motivation (P-value 0.000). Male students (52 people) have a balanced distribution between moderate and high categories, while women (56 people) are more dominant in the moderate category (40 people). Non-exact students (80 people) are more in the high category (30 people) than exact students (12 out of 28 people). Achievement motivation is influenced by factors such as academic load and self-development opportunities. In conclusion, student motivation is influenced by learning methods, academic environment, and social factors. Recommendations include implementing programs such as mentoring, self-development training, and learning innovation.